Managing at the speed of change : how resilient managers succeed and prosper where others fail - Conner, Daryl R. (New York Random House, 1993)
This classic, newly updated, is an indispensable source for anyone?from mid-level managers to CEOs?who must execute key business initiatives quickly and effectively. Once groundbreaking and now time-honored, Managing at the Speed of Change has helped countless business leaders learn how to orchestrate transitions vital to their organizations'success. Rather than focusing on what to change, this book's aim is far more valuable: It shows readers how to change.Daryl R. Conner, founder and chairman of the consulting firm Conner Partners, is a leading expert on change management. He has served as “change doctor” for clients that include non-profit enterprises, government agencies and administrations, and Fortune 500 companies in an array of industries such as Abbott Laboratories, PepsiCo, American Express, Catholic Healthcare West, JPMorgan Chase, and the U.S. Navy.Based on Conner's long-term research and his decades of consulting experience, Managing at the Speed of Change uses simple, easy-to-understand language and elegant visuals to explore the dynamics of change, and in doing so, teaches readers? why major change is difficult to assimilate? what distinguishes resilient individuals from those who suffer future shock? how and why resistance forms? how people become committed to change? why organizational culture is so important to the success of change? the roles most central to change in organizational settings? why powerful teamwork is at the heart of achieving change objectives, and how to foster itIn this pioneering book, updated for the twenty-first century, Conner demonstrates how both individuals and organizations can develop the capacity not only to endure change but to thrive on it.
Keywords: Cambio organizacional; Libros electrónicos